Spacecraft attitude dynamics - Hughes, Peter C. 1940- (Dover Books on Aeronautical Engineering Ser., 2004)
From its roots in classical mechanics and reliance on stability theory to the evolution of practical stabilization ideas, this volume covers environmental torques encountered in space; energy dissipation; motion equations for four archetypical systems; orientation parameters; illustrations of key concepts with on-orbit flight data; and typical engineering hardware. 1986 edition.